PROSPECTS OF MEDIATION AS AN ALTERNATIVE DISPUTE RESOLUTION MECHANISM IN THE UAE CONSTRUCTION INDUSTRY - KHAN, HASEEB DAD (2018)
Every construction project is in actual unique due to the fact that the variables of cost, time, quality, conditions and contractual risks are never consistent from one project to the next, and thus it would not be logical to think that the causes of construction disputes could be contained using a certain set of contracting principles or wording. Further, the human element involved in the execution of construction contracts coming from different parts of the world adds to the possibility of disputes and conflict. Though, dispute avoidance techniques are utilized, but disputes cannot be avoided in many circumstances and thus a requirement of dispute resolution methods. In the last twenty years there has been made development and are many recognized ADR methods apart from litigation available now to the contracting parties. Mediation is one of the ADR methods available, which has developed significantly and been adopted by many mature economies such as US, UK, Australia etc. However, in the UAE the process is not widely adapted as a method of ADR. From experience UAE Employers and Contractors consider only arbitration and litigation to resolve disputes, this dissertation will look into the reasoning behind it and why. The aim of this dissertation is to investigate the factors UAE construction professionals take into consideration while finalizing the dispute resolution method and if the current methods of dispute resolution adopted under UAE construction contracts are no longer sufficient to meet the needs of the construction industry and whether alternatives such as Mediation the answer. Parties to a construction contract want a dispute resolution method that is speedy, less costly, flexible and preserves the business relationship between the parties. It can be argued that Mediation meets this criterion and prevents to a higher degree in disputes reaching to more contentious levels of resolution such as arbitration and litigation. This dissertation explores the benefits Mediation has to offer in the context of the UAE construction industry by reviewing international publications, literature in text books and data available on the subject in the market. In addition, an on-line survey was conducted to gather a detailed opinion of the construction professionals in the UAE on Mediation as a potential primary dispute resolution mechanism, as well as semi-structured interviews were carried out with legal and construction professionals to understand why Mediation is currently not widely being utilized in the UAE and what measures need to be adopted to overcome these obstacles. Change in industry culture, education, training, government initiative and participation (Arbitration Act), genuine intent to resolve are needed in order for Mediation to find traction in the UAE construction industry.